A Child with Acute Appendicitis Secondary to Blunt Abdominal Trauma: A Case Report and Review of the Literature - Aykut Çağlar; Anıl Er; Özge Atacan; Pelin Gülcü; Sinan Genç; İlknur Çağlar; Tanju Çelik; Hurşit Apa (Galenos Yayinevi, 2018)
We present a child with abdominal pain and vomiting after blunt abdominal trauma (BAT). He had tenderness, guarding and rebound on the bilateral lower quadrant of the abdomen. He had no abrasion on the abdominal skin surface. He had marked leukocytosis and increased C-reactive protein level. Contrast-enhanced abdominal computed tomography revealed inflamed appendicitis. He was operated by pediatric surgeons and, an perforated appendix was illustrated on pathological examination. BAT and acute appendicitis (AA) are independently very frequent issues. In pediatric emergency departments, BAT and AA are very frequent issues, however, coexistence of these two condition in the same patient is rare. This case report and review of the literature showed that occurrence of AA after BAT should be considered by emergency physicians.